Diagrammatic scale for the assessment of blast on wheat spikes - Maciel,João Leodato Nunes (2013)
The correct quantification of blast caused by the fungus Magnaporthe oryzae on wheat (Triticum aestivum) spikes is an important component to understand the development of this disease aimed at its control. Visual quantification based on a diagrammatic scale can be a practical and efficient strategy that has already proven to be useful against several plant pathosystems, including diseases affecting wheat spikes like glume blotch and fusarium head blight. Spikes showing different disease severity values were collected from a wheat field with the aim of elaborating a diagrammatic scale to quantify blast severity on wheat spikes. The spikes were photographed and blast severity was determined by using resources of the software ImageJ. A diagrammatic scale was developed with the following disease severity values: 3.7, 7.5, 21.4, 30.5, 43.8, 57.3, 68.1, 86.0, and 100.0%. An asymptomatic spike was added to the scale. Scale validation was performed by eight people who estimated blast severity by using digitalized images of 40 wheat spikes. The precision and the accuracy of the evaluations varied according to the rater (0.82<R²<0.90, -6.12<a<2.94, 0.85<b<1.16), and systematic errors in overestimating or underestimating the disease were not found among the raters, demonstrating that the developed scale is suitable to evaluate blast on wheat spikes.